2017
DOI: 10.1186/s13018-017-0673-1
|View full text |Cite
|
Sign up to set email alerts
|

The medial femoral wall can play a more important role in unstable intertrochanteric fractures compared with lateral femoral wall: a biomechanical study

Abstract: BackgroundThe major objective of the present study is to investigate the differences in the load and strain changes in the intertrochanteric region of human cadaveric femora between the loss of medial or lateral wall and after treatment with proximal femoral nail antirotation (PFNA).MethodsAfter measuring the geometry of the proximal femur region and modeling the medial or lateral wall defect femoral models, six pairs of freshly frozen human femora were randomly assigned in the medial or lateral wall group. Ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 19 publications
2
27
0
Order By: Relevance
“…Due to the relatively poor bone quality and quantity in the affected side, premature weight-bearing could result in failed internal fixation and screw loosening. Some authors [ 12 , 21 ] have reported that coxa vara deformity often occurs after locking compression plate internal fixation due to severe osteoporosis and weight-bearing activity before the internal femoral cortex establishes adequate buttress function. For this reason, the standing timing and weight-bearing for such patients needs to be determined according to the type of fracture, osteoporosis, and fracture healing conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the relatively poor bone quality and quantity in the affected side, premature weight-bearing could result in failed internal fixation and screw loosening. Some authors [ 12 , 21 ] have reported that coxa vara deformity often occurs after locking compression plate internal fixation due to severe osteoporosis and weight-bearing activity before the internal femoral cortex establishes adequate buttress function. For this reason, the standing timing and weight-bearing for such patients needs to be determined according to the type of fracture, osteoporosis, and fracture healing conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The medial wall consisted of the medial cortex and medial calcar located in its deep side. The loss of the medial support had been proven to cause coxa varus postoperatively due to the hinge [23]. When a lateral wall fracture occurred, the medial support played a important role in maintaining the stability of the intertrochanteric fracture.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have proven that the condition of the lateral wall most signi cantly affects the e cacy of the device used for unstable ITFs, followed by the integrity of the medial and lateral wall of the trochanteric region [4][5][6] . While cephalic intramedullary nails have been regarded as more reliable than Dynamic Hip Screws for unstable ITFs, there is still controversy when encountering fractures with preserved lateral walls.…”
Section: Introductionmentioning
confidence: 99%